(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: The presentation of corona virus disease 2019 (COVID-19) may include neurological features and patients with neurological disorders may develop concomitant COVID-19 during pandemic. Hyperglycemia leads to higher propensity to COVID-19 infection with higher disease severity. Objective: To assess the neurological diagnoses, glycemic status and outcome in patients hospitalized primarily for neurological problems and subsequently diagnosed as COVID-19. Methods: This retrospective cohort study was conducted in National Institute of Neurosciences (NINS) & Hospital, Dhaka, Bangladesh. Patients admitted to adult Neurology ward during April to November 2020 primarily for neurological problems and diagnosed as confirmed COVID-19 (with positive RT-PCR test for COVID-19) were included. The hospital records were reviewed and recorded in a checklist. Outcome of patients referred to COVID-19 dedicated hospitals was obtained over telephone. Results: The study included 85 patients with COVID-19 [median age 60 years (IQR: 45-65); 63.5% male]. Acute ischemic stroke was the most common neurological diagnosis (32.9%), followed by acute hemorrhagic stroke and subarachnoid hemorrhage (22.4% and 15.3% respectively). Other neurological diagnoses were meningoencephalitis (7.1%), Guillain Barre Syndrome (4.7%), Myasthania Gravis (1.2%), brain abscess (1.2%) and intracranial space occupying lesion (1.2%). Fourteen percent patients had no definite neurological diagnosis, they were admitted for delirium. History of diabetes was present in 18% patients. The mortality was 27% and the proportion of mortality was significantly higher in patients known to have DM in comparison to those who were not (p=0.012). The mean age and proportion of male sex was significantly higher among those who expired. Conclusion: There is high rate of mortality in neurological patients with COVID-19 who have variable neurological diagnosis including stroke, autoimmune disease and cerebral infections. Co-existent diabetes further increases the rate of mortality. Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 97-102